Aquaporin-9 Contributes to the Maturation Process and Inflammatory Cytokine Secretion of Murine Dendritic Cells - De Santis, Stefania; Serino, Grazia; Fiorentino, Maria R.; Galleggiante, Vanessa; Gena, Patrizia; Verna, Giulio; Liso, Marina; Massaro, Monica; Lan, Jinggang; Troisi, Jacopo; Cataldo, Ilaria; Bertamino, Alessia; et al. (Frontiers in Immunology, 2018)
Dendritic cells (DCs) are the most potent antigen-presenting cells able to trigger the adaptive immune response to specific antigens. When non-self-antigens are captured, DCs switch from an “immature” to a “mature” state to fulfill their function. Among the several surface proteins involved in DCs maturation, the role of aquaporins (AQPs) is still poorly understood. Here we investigated the expression profile of Aqps in murine bone marrow derived dendritic cells (BMDCs). Among the Aqps analyzed, Aqp9 was the most expressed by DCs. Its expression level was significantly upregulated 6h following LPS exposure. Chemical inhibition of Aqp9 led to a decreased inflammatory cytokines secretion, due to a reduced glycerol intake. BMDCs from AQP9-KO mice release lower amount of inflammatory cytokines and chemokines and increased release of IL-10. Despite the reduced release of inflammatory cytokines, Aqp9-KO mice were not protected from DSS induced colitis. All together, our data indicate that AQP9 blockade can be an efficient strategy to reduce DCs inflammatory response but it is not sufficient to protect from acute inflammatory insults such as DSS induced colitis.